Manifestations of Toxic Masculinity in Cormac McCarthy’s Blood Meridian or the Evening Redness in the West - Vahit Yaşayan (American Studies in Scandinavia, 2021)
This article analyzes Blood Meridian or The Evening Redness in the West (1985)—the first product of Cormac McCarthy’s borderlands immersion—by deploying the concept of “toxic masculinity,” an exaggerated masculinity related mythically to the role of the cowboy/warrior/pioneer, which creates recklessness and eventually perpetuates violence. In other words, it explores how perfunctorily embracing, or endeavoring to fulfill, hegemonic masculine ideals bring about self-destructive behaviors in McCarthy’s monolithically male characters on the Texas-Mexico border in the 1850s. Even though the term “toxic masculinity” was seldomly used in the 1980s when McCarthy wrote this novel, he clearly anticipates and historicizes the evolution of American masculinity as embodied by the cowboy/warrior/pioneer into a form of toxic masculinity. By doing so, he presages the gradual cultural recognition that such masculinity is not the generic standard against which all versions of gendered identity should be measured but is in fact toxic, pathological, political, and problematic. By exposing toxic cowboy mythology and deploying it to construct alternative masculinities, McCarthy questions the Frontier Thesis and Manifest Destiny while disrupting the toxic assumptions about manhood and masculine identities they were intended to uphold. The new vision McCarthy presents in Blood Meridian challenges the development of American national identity based on the vicious conquest of impoverished, discriminated, oppressed, and racialized Others and exploited, feminized nature.